Congenital Diaphragmatic Hernia: Atypical Early X-Ray Presentation - A. Wasey, Waiz; Kumar Srivastava, Shashank (International Journal of Medical Research and Review, 2014)
Congenital Diaphragmatic Hernia (CDH) is a congenital malformation of the diaphragm that allows herniation of the abdominal organs into the thoracic cavity. The most common type of CDH is Bochdalek Hernia. It is seen commonly on the left side than right, the right side being protected by the liver. CDH is a life threatening condition, most likely due to pulmonary hypoplasia. We report a left sided Bochdalek Hernia in a preterm female newborn delivered by Caesarian section.